2021
DOI: 10.51372/bioagro333.4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and grain yield stability of rice hybrids and varieties in Venezuela

Abstract: The development of new high-performance and stable cultivars requires test multi-environmental validation to deal with the effect of genotype by environment interaction (GEI). With the objective to determine adaptability and stability for grain yield in hybrids and rice varieties through the models AMMI, SREG and REML/BLUP. Six experiments were evaluated during the 2015-2016 dry season in the main producing regions of Venezuela. The ANOVA detected differences for genotype (G), environment (E) and their interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Consequently, all the interaction information could be speculated by plotting these two PCs. Our findings provide proofing for the results of several earlier investigations obtained by others that support the idea that the first two IPCs of the AMMI model are the most important during quantifying GEI [ 14 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, all the interaction information could be speculated by plotting these two PCs. Our findings provide proofing for the results of several earlier investigations obtained by others that support the idea that the first two IPCs of the AMMI model are the most important during quantifying GEI [ 14 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…These variability among the environmental conditions may have activated some yield-enhancing genes in different genotypes, which developed a significant GEI and resulted in high yield variability ( Figure 1 A,B). While investigating the genotypic yield stability across environments, the research reported by Barona et al 2021, Dewi et al 2014, Tariku et al 2013, and Zewdu et al 2020 [ 34 , 35 , 36 , 37 ] also concluded that the environmental effect recorded the highest impact. Meanwhile, other investigations reported genotypes’ effects to be the most effective impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Los testigos SD20A y PIONERO también fueron utilizados por Acevedo et al (2021), para determinar la adaptabilidad y estabilidad del rendimiento de granos de seis híbridos y cuatro variedades de arroz a través del uso de tres modelos multivariados, donde la variedad PIONERO resultó con alta estabilidad fenotípica, pero con rendimientos moderados, mientras que SD20A obtuvo altos rendimientos, pero con adaptación específica a uno de los ambientes utilizados en el estudio. También Delgado et al (2021), evaluaron 50 líneas avanzadas de arroz más un testigo en condiciones de sabanas de Colombia, logrando identificar dos líneas que superaron en rendimiento de manera significativa al testigo.…”
Section: Tablaunclassified
“…Recent studies describe the predicting efficiency of AMMI and GGE biplots by using the genotype average yield, the relationship between genotypes and the evaluation of the environments (Acevedo et al, 2021;Acevedo et al, 2019;Rebolledo et al, 2018;Haider et al, 2017;Akter et al, 2015). Nevertheless, few publications are available in Venezuela and Latin America on rice hybrid GEI research.…”
Section: Introductionmentioning
confidence: 99%